Sustainability as Cognitive “Friction”: A Narrative Approach to Understand the Moral Dissonance of Sustainability and Harmonization Strategies - Weder, Franzisca; Tungarat, Amornpan; Lemke, Stella (Frontiers in Communication, 2020)
Narratives represent storied ways of knowing and communicating, thus, have always been a key feature in media and communication research. In our contribution, a concept to explain sustainability related cognitivei dissonances as well as a new version of a narrative inquiry is introduced to capture reflections on experiences of sustainability and individual assessments of (un)sustainable behavior over time. We perceive storytelling as an action, as act of problematization which uncovers cognitive dissonances and coping strategies. Using Rory’s Story Cubes® (dice with pictograms), we stimulated 35 interviewees from various cultural backgrounds (Asian, European, Anglo-American) to “story” sustainability related life events into order and meaning. Our evaluation of the interviews focused on the story as a whole, which was then linked to the individual biographical background to understand motives for and moral conflicts about (un)sustainable behavior. In this paper, we want to put this theoretical concept and the related innovative inquiry-form up for discussion for environmental communication research for a better understanding of individual perceptions of sustainability, moral dissonances and cognitive friction occurring in relation to sustainability related issues.